Occlusal hypofunction affects the gene expression of osteoblast and primary cilia in the alveolar bone: An experimental study - HU Lingwei; SUN Yao (Kouqiang hemian waike zazhi)
[Objective:] To investigate whether the gene expression changes of the primary cilia and osteoblast in the alveolar bone are associated with occlusal hypofunction. [Methods:] The unloading model was established in the right mandible on 6-week-old wild type (WT) male mice and the left side was used as a self-control study. Samples were sacrificed 2 weeks after the operation, and the parameters of alveolar bone were scanned and analyzed by micro-CT. The changes in the number and position of osteoblasts and osteoclasts were observed histologically, and real-time quantitative polymerase chain reaction (RT-qPCR) was used to detect the expression of osteoblastogenesis and osteoclastogenesis. The changes in the number and location of primary cilia were observed by co-staining, and the expression of cilium-related genes was detected. The Pearson correlation analysis was used to detect the expression of cilium-related genes and osteoblastogenesis, and the colocalization was observed by co-staining. [Results:] Analysis of the unloading side revealed a significant decrease in bone volume/total volume (BV/TV) (P<0.05). The number of osteoblasts decreased while the number of osteoclasts increased significantly (P<0.01). Both the occurrence rate of primary cilia and expression of cilium-related genes showed a decreasing trend (P<0.05). Furthermore, the expression of osteoblastogenesis and intraflagellar transport genes were significantly correlated (P<0.05). Co-staining results showed that osteoblasts were located on the top of root furcation, and there were primary cilia on the surface. [Conclusion:] The parameters of alveolar bone on the experimental side were significantly decreased and bone resorption accelerated on the unloading side. Both the number of osteoblasts and primary cilia as well as the expression of related genes decreased significantly and the expression levels of related genes were positively correlated.